2022
DOI: 10.56093/ijans.v92i2.122097
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric discrimination in Bali cattle (Bos javanicus) at two different altitude areas of Jambi province, Indonesia

Abstract: Bali cattle (Bos javanicus) is an important livestock for the farmers at Jambi Province of Indonesia for meat production purposes. This research was aimed to classify adult Bali cattle (about 3.5 years age) based on their body measurements (morphometrics). The animals in this study were collected from two different altitude areas (lowland and midland) of Jambi province. A canonical discriminant analysis (CDA) was computed in this study for discrimination of animals. A total of 480 animals collected from lowlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Most of the correlations in Bali dan Limbal Cattle are below 0.4 in which it is a weak correlation and indicates that the body measurements are very diverse or not consistent with each other. This result is in contrast with the previous study which reported that almost all body morphometrics of Bali Cattle have a high correlation (Depison et al, 2022). However, it is in agreement with the previous study reported that Bali Cattle body measurements have a low correlation (Khasanah et al, 2020) and Simbal has a high correlation (Almakmum et al, 2021).…”
Section: Body Morphometrics and Reproduction Performancesupporting
confidence: 58%
See 2 more Smart Citations
“…Most of the correlations in Bali dan Limbal Cattle are below 0.4 in which it is a weak correlation and indicates that the body measurements are very diverse or not consistent with each other. This result is in contrast with the previous study which reported that almost all body morphometrics of Bali Cattle have a high correlation (Depison et al, 2022). However, it is in agreement with the previous study reported that Bali Cattle body measurements have a low correlation (Khasanah et al, 2020) and Simbal has a high correlation (Almakmum et al, 2021).…”
Section: Body Morphometrics and Reproduction Performancesupporting
confidence: 58%
“…Whereas, CCA is used to investigate the relationship between two sets of variables (Timm, 2007). Multivariate analysis in Bali Cattle body measurement has been done by previous studies using PCA (Wilastra et al, 2021) and CDA (Depison et al, 2022). However, no study has addressed the relationship between the body morphometrics of Bali and Bali Cross with their reproductive trait simultaneously.…”
Section: Advances Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter yang diukur pada dimensi tubuh meliputi: lingkar dada, tinggi pundak, panjang badan, tinggi pinggul, lebar dada dan lebar pinggul. Pengukuran dimensi tubuh dilakukan menggunakan tongkat ukur dan meteran (Bahri et al, 2022;Depison et al, 2022;Gde et al, 2016).…”
Section: Parameter Yang Diukurunclassified
“…Hal ini sesuai dengan pendapat (Depison et al, 2020;Ismirandy, 2018) bahwa pada umur 1,5-2,5 tahun merupakan fase pertumbuhan tulang dan mencapai puncak pertumbuhan tulang pada umur 3 tahun. Hal ini sesuai dengan pendapat (Bagiarta et al, 2017;Depison et al, 2022;Ismirandy, 2018;Sri Rachma et al, 2011) menjelaskan bahwa jika telah mencapai kedewasaan pada fase pubertas dilanjutkan dengan dewasa tubuh makan pertumbuhannya telah terhenti, jika ternak mengalami perubahan maka perubahan tersebut karena penimbunan lemak bukan pertumbuhan masa otot murni, kondisi ini perlu menjadi bahan pertimbangan pada saat kita memilih bakalan sapi untuk penggemukan yang berorientasi pada kualitas daging.…”
Section: Lebar Pinggulunclassified